(untitled) (Research, Society and Development, 2022)
The purpose of this study was to analyze the risk factors associated with eating behavior in climacteric women assisted in Primary Health Care. Methods: This is a cross-sectional study with a random sample composed of 874 women aged between 40 and 65 years assisted in Family Health Strategies units in Montes Claros, Minas Gerais, Brazil. The following variables were investigated: sociodemographic, menopausal and behavioral characteristics. The outcome was food consumption, a score was created and dichotomized into healthy and unhealthy, with the cut-off point being the mean value. Descriptive analyzes of all variables were performed, as well as bivariate analyzes using the chi-square test. After being selected for multiple analysis, the Poisson regression model with robust variance was used, in a hierarchical manner consisting of blocks of variables at distal, intermediate and proximal levels. At the distal level, income below one minimum wage (PR=1.33) was associated with unhealthy eating behavior. At the intermediate level, the variables that remained associated with the outcome after adjustment were perimenopausal climacteric (PR=0.75) and no menstruation in the last 12 months (PR=0.68). At the proximal level, alcoholism (PR=1.35) and sedentary lifestyle (PR=1.52) remained significantly associated with food consumption. Climacteric women showed a relevant prevalence of unhealthy eating behavior associated with sociodemographic, climacteric and lifestyle characteristics.